Formalizacja ontologii ufundowania - Rosiak, Marek (Filozofia Nauki, 1996)
The paper refers to the author's informal considerations from his article „The ontology of founding” (published in „Filozofia Nauki”, 1995, no 1-2). The starting point of the paper is a definition of „monadic whole”, i.e. such a whole, which contains no elements mutually linked up by moments of unity. Then definitions of „part stricto sensu”, „whole (in general)”, „identity of two wholes” etc., are formulated. Using the conceptual apparatus, introduced by these definitions, the author gives some theorems withoutlines of their proofs. In conclusion, the explicative power of the presented formalization with reference to remaining categorial notions of ontology (i.e. notions of property, relation, universals), and in comparison to some other modern theories of parts and wholes, is discussed.